Hepatic and serum folates in patients fasting and after oral folic acid. Issue 2 (March 1971) - Dawson, D. W.; Geary, C.
Abstract : The hepatic folate in non-anaemic hospital patients was found to correlate poorly with the fasting serum folate. The rise in methylfolate in the systemic circulation following the absorption of folic acid was directly related to the folate content of the liver.